"Faith in the world" : post-secular readings of Hannah Arendt - The Cryptotheological Legacy of Hannah Arendt; Zawisza, Rafael HerausgeberIn; Hagedorn, Ludger 1967- HerausgeberIn; Campus Verlag (Campus Verlag, 2021)
This volume offer a manifold approach to a less evident and until now much neglected undercurrent in the work of Hannah Arendt., namely her ambiguous relation to the Judeo-Christian relligious heritage. Arendt's dissertation was dedicated to the concept of love in the works of Augustine, where she set her tone and developmed her frame for approaching theological matters. Her understanding of secularity might provide a model for the reconciliation of secularization and the persistence of religious belief in the contemporary world. Thought Hannah Arendt wad certainly and outspokenly a secular thinker, her work also harbors ways of understanding secularization as the possibility of a new, maybe even messianic, attitude towards finite life and earthly reality. She famously depicts this attitude as "faith in and hope for the world". --Book cover